OC 8459 Assessment of parasite clearance after repeated treatment with artesunate amodiaquine, dihydroartemisinin-piperaquine, pyronaridine-artesunate in malaria patients in burkina faso. (24th April 2019) - Soulama, Issiaka; Sirima, Sodiomon B
Abstract : Background: Reports from Southeast Asia showed delayed parasite clearance after treatment with known artemisinin-based combination therapies (ACTs), the first-line treatment for malaria. We then carried out a study in the framework of the WANECAM clinical trial to assess comparatively the parasite clearance time and rate from P. falciparum malaria patients repeatedly treated with the artesunate-amodiaquine (ASAQ), dihydroartemisinin-piperaquine (DHA-PQ) and artesunate-pyronaridine (PYR). Methods: A randomised, phase III/IV comparative, multicentre, open-label, parallel 3-arms trial was conducted in Banfora Health District area comparing the efficacy of a three-day regimen of DHA-PQ, PYR with ASAQ for the treatment of children (above 6 months) and adults with uncomplicated falciparum malaria. From August 2012 to December 2013, each randomised patient was followed up for 42 days over a period of two years. Treatment was directly observed, and blood smear samples were collected twice daily (12 hour±2 hour) until parasite clearance. The endpoints of the present sub-study were parasite clearance rate and time. The secondary endpoints included PCR-corrected and uncorrected cure rates. Results: Out of 2843 screened patients, 763 were recruited for parasite clearance endpoint analyses. The median parasite clearance time (PCT) was 24.1 hour (2-sided 95% CI, 24.0 to 24.2 hour), 23.9 hour (2-sided 95% CI, 23.8 to 24.0 hour) and 24.2 hour (2-sided 95% CI, 24.1 to 24.5 hour), in PYR and DHA-PQ, respectively. The PCR-corrected efficacy rates were estimated at 99.8%; 99.7%; 99.9%, at day 28% and 99.3%; 99.7%–99.9% in PYR, ASAQ and DHA-PQ, respectively. Conclusion: The parasite clearance times were comparable among the three ACT arms of treatment and their efficacy was comparable and higher than 99%. There was no delay in parasite clearance time (PCT ≥72 hour).